Diminished spectrin extraction from ATP-depleted human erythrocytes. Evidence relating spectrin to changes in erythrocyte shape and deformability. - Lux, S E (1978)
We measured spectrin "extractability" in erythrocytes which were metabolically depleted by incubation at 37 degrees C in plasma or glucose-free buffers. Membranes were extracted with 1 mM EDTA (pH 8, 40 h, 4 degrees C) and analyzed by polyacrylamide gel electrophoresis in sodium dodecyl sulfate. This procedure solubilized 85--90% of the spectrin, actin, and residual hemoglobin from ghosts of fresh erythrocytes. In incubated erythrocytes, inextractable spectrin rapidly accumulated when ATP concentrations fell below 0--15% of normal. In severely depleted cells, 60--90% of the total ghost spectrin became inextractable. Inextractability was not abolished by physically disrupting the ghost before extraction, but was reversed when erythrocyte ATP was replenished with adenosine. The accumulation of inextractable spectrin correlated temporally with the increase in apparent membrane deformability and the increases in erythrocyte vicosity, calcium content, sodium gain, and potassium loss characteristic of ATP-depleted erythrocytes. No change in integral membrane protein topography (assessed by the distribution of intramembranous particles and concanavalin A surface-binding sites) was detected in depleted cells. Analogous changes were observed in erythrocytes exposed to extremes of pH and temperature. When the pH in the erythrocyte interior fell below 5.5, a pH where spectrin was aggregated and isoelectrically precipitated, erythrocyte and ghost viscosity increased coincident with a marked decrease in spectrin extractability. Similarly above 49 degrees C, a temperature where spectrin was denatured and precipitated, erythrocyte viscosity rose as inextractable spectrin accumulated. These observations provide direct evidence of a change in the physical state of spectrin associated with a change in erythrocyte shape and deformability. They support the concept that erythrocyte shape and deformability are largely determined by the shape and deformability of the spectrin-actin protein meshwork which laminates the inner membrane surface.